In vitro biological activity of extracts and compounds from Ptaeroxylon obliquum (Thunb.) Radlk. against oral strains of Candida albicans - Botha, Francien Susanna (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.